Looking into dark matter with asteroseismology - Ayala, Adrián (Frontiers in Astronomy and Space Sciences, 2022)
Dark matter remains as an elusive component of modern Cosmology. According to previous research, stellar physics observables can be affected by the presence of hypothetical dark matter particles, which can be produced or accreted into the stars. Stellar pulsations are among the observables affected by dark matter, because the changes of the internal structure of the stars due to dark matter produce variations in the pulsation frequencies. We review the current research in the interplay between astroparticles, precise stellar observations, and accurate asteroseismic models, which can be extremely useful in order to constrain dark matter candidates from asteroseismic observables.